EFFECTS OF SCHOOL-BASED LIFE SKILLS TRAINING ON VIOLENCE AND HEALTH RISK BEHAVIOURS AMONG IN-SCHOOL ADOLESCENTS IN DELTA STATE (2016)
Secondary school adolescents in Delta State are increasingly engaging in violence and health-risk behaviours which negatively affect their cognitive performance, emotions, choices and overall quality of life. This trend warranted the integration of life-Skills into the secondary school curriculum with a view to changing the in-school adolescents’ negative behaviours. Previous studies have shown non implementation of life-Skills training included in the school curriculum in Delta State; hence the continued occurrence of violence and health-risk behaviours among the students. This study, therefore, determined the effects of school-based life-Skills (interpersonal Skills and problem-solving Skills) training on violence and health-risk behaviours of in-school adolescents in Delta State, Nigeria. The moderating effects of gender and religion were also examined. The study adopted pretest-posttest control group, quasi experimental design with a 3x2x2 factorial matrix. The social learning and ecological theories were adopted for the study. Purposive sampling technique was used to select one co-education public secondary school with large student population from each of the three senatorial districts. Two hundred and sixteen (116 and 100 female) Senior Secondary I and II students with records of violence and health-risk behaviour in the three schools were purposively selected. Participants were randomly assigned to interpersonal Skills training, problem solving Skills training and the conventional groups. The training lasted eight weeks. Adolescents Violence Behaviour (r=0.81), Adolescents health-risk behaviour (r=0.76) questionnaires and Interpersonal and problem-solving Skills training manuals were used for data collection. Data were analyzed using Analysis of Covariance and Sheffe post-hoc test at 0.05 level of significance. Treatment had a significant main effect on in-school adolescents’ violence (F(2,204)=34.67; n2=0.25) and health risk behaviour (F(2,204)=19.06; n2=0.16). Adolescents exposed to problem-solving Skills training had the lowest reduction in violence ( =64.04) and health-risk behaviour reduction ( =98.07) than those exposed to interpersonal Skills (violence = =51.81; health risk = =88.33) and control group (violence = =43.43; health risk= =74.81). There were no significant main effects of gender and religion on violence and health-risk behaviours among adolescents. The two-way interaction effects of treatment and gender on violence behaviour was significant (F(2,204)=5.05; n2=0.047, P<0.05), and not significant on health-risk behaviour. The two-way interaction effect of treatment and religion was not significant on both violence and health-risk behaviour. The three-way interaction effects of treatment, gender and religion on violence and health risk-behaviour was not significant. Problem-solving Skills and interpersonal Skills trainings were effective strategies for reducing violence and health risk behaviours among in-school adolescents in Delta State, Nigeria. Secondary school students therefore should be exposed to the two life-Skills training, regardless of gender and religion